Does sex interact with the 2D:4D ratio or adult circulating hormones on the estimated glomerular filtration rate? A cross‐sectional study in Ghana - Moses Banyeh; Kervin Edinam Zogli; Hisham Alhassan Osumanu; Lawrence Obeng; Tuah Kwabena Acheampong; Clement Binwatin Dagungong; Elizabeth Bayor; Nafiu Amidu (Physiological Reports, 2022)
Abstract The 2D:4D ratio is the putative marker of prenatal hormone exposure and has been suggested as a correlate of adult circulating testosterone and estrogen. The study aimed to determine whether sexual dimorphism in the estimated glomerular filtration rate (eGFR) can be partly explained by the 2D:4D ratio or adult circulating testosterone or estrogen. The study was cross‐sectional from June to December 2021 at the University for Development Studies. The study involved 206 healthy adults (Female = 93, Male = 113) between 18 and 30 years. The 2D:4D ratio was measured using computer‐assisted analysis. Venous blood samples were collected and analyzed for testosterone, estradiol and creatinine using the ELISA technique and routine biochemical analysis. The adjusted eGFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) creatinine equation (2021). The eGFR and the testosterone‐to‐estradiol ratio (TT:E2) were significantly higher in males than in females (p < 0.001). There was a significant interaction between sex and the TT:E2 on the eGFR (p < 0.001). Although the relationship between the eGFR and the TT:E2 was negative in both males and females, a unit change in the TT:E2 had a greater impact on the eGFR in females (B = −1.38) than in males (B = −0.01). Sexual dimorphism in the eGFR is influenced by both testosterone and estradiol. Although the sex difference in the eGFR may be influenced by the TT:E2, estrogen seems to account for more variability in the eGFR than testosterone.